The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/cbdv.201700211
|View full text |Cite
|
Sign up to set email alerts
|

Transformations of Some Sesquiterpene Lactones by Filamentous Fungi and Cytotoxic Evaluations

Abstract: Biotransformation is an economically and ecologically viable technology which has been used to modify the structures of many classes of biologically active products. Some fungi may be useful for the biotransformation of sesquiterpene lactones (SLs), leading to unusual structural changes that modify their biological activities, and other transformations mimic their biosynthetic pathways, generating evidences for the proposed biogenesis. Eight filamentous fungi were screened for their ability to transform differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The 1 H– 1 H COSY correlations of H 2 -2/H-3/H-4 (Figure ), together with the HMBC correlations (Figure ) from H-3 (δ H 3.16) to C-1 (δ C 77.3), C-2 (δ C 32.7), C-4 (δ C 62.4), and C-5 (δ C 73.9) and from H-4 (δ H 2.90) to C-3 (δ C 53.0), C-5, C-6 (δ C 39.9), and C-10 (δ C 43.5), indicated the O -bearing feature of C-3 and C-4. However, compared with other hydroxyl-substituted methines, C-3 and C-4 appeared in the higher field, which suggested that the epoxy moiety existed between C-3 and C-4. , It is also common to produce epoxy moieties during biotransformation. In addition, the presence of 5-OH was established based on a series of HMBC cross-peaks of H-4, H 2 -6, H 2 -9, and Me-13 with C-5. The NOE correlations of H-3/Me-15 and H-4/Me-15 (Figure ), in combination with the coupling constant of H-3 and H-4 ( J = 4.2 Hz), , supported the α-orientation of the epoxy fragment.…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H– 1 H COSY correlations of H 2 -2/H-3/H-4 (Figure ), together with the HMBC correlations (Figure ) from H-3 (δ H 3.16) to C-1 (δ C 77.3), C-2 (δ C 32.7), C-4 (δ C 62.4), and C-5 (δ C 73.9) and from H-4 (δ H 2.90) to C-3 (δ C 53.0), C-5, C-6 (δ C 39.9), and C-10 (δ C 43.5), indicated the O -bearing feature of C-3 and C-4. However, compared with other hydroxyl-substituted methines, C-3 and C-4 appeared in the higher field, which suggested that the epoxy moiety existed between C-3 and C-4. , It is also common to produce epoxy moieties during biotransformation. In addition, the presence of 5-OH was established based on a series of HMBC cross-peaks of H-4, H 2 -6, H 2 -9, and Me-13 with C-5. The NOE correlations of H-3/Me-15 and H-4/Me-15 (Figure ), in combination with the coupling constant of H-3 and H-4 ( J = 4.2 Hz), , supported the α-orientation of the epoxy fragment.…”
Section: Resultsmentioning
confidence: 99%
“…These are usually lactones containing in their structure, apart from methyl groups, halogen atoms, or double bond. The most common products of such reactions are hydroxyl derivatives of lactones [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%